2017
DOI: 10.1007/s11218-017-9410-1
|View full text |Cite
|
Sign up to set email alerts
|

Basic psychological needs and school engagement: a focus on justice and agency

Abstract: In this paper, we examine the relationship between basic psychological needs and student engagement in a population of Italian secondary school students. To measure the psychological needs, we have selected a set of indicators that, beyond the needs for autonomy, competence and relatedness, also include the need for justice, which is crucial in adolescence when the degree of sensitivity to the ways people behave in interpersonal interactions is well developed. To measure student engagement, we have considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 40 publications
7
44
0
Order By: Relevance
“…Another result to emerge from this study was the role of satisfaction at school as a mediator between number of absences and perceived teacher support. This result, again consistent with other studies (Niemiec and Ryan, 2009; Yu et al, 2015; Malu and Reddy, 2016; Molinari and Mameli, 2018), suggests that when teachers pay attention to their students’ point of view, they support their need to feel free to choose, be competent, and be connected with others, thus increasing their involvement at school and reducing the number of absences.…”
Section: Discussionsupporting
confidence: 90%
“…Another result to emerge from this study was the role of satisfaction at school as a mediator between number of absences and perceived teacher support. This result, again consistent with other studies (Niemiec and Ryan, 2009; Yu et al, 2015; Malu and Reddy, 2016; Molinari and Mameli, 2018), suggests that when teachers pay attention to their students’ point of view, they support their need to feel free to choose, be competent, and be connected with others, thus increasing their involvement at school and reducing the number of absences.…”
Section: Discussionsupporting
confidence: 90%
“…In a study on students' perceptions of the classroom learning environment, Tas (2016) showed that justice (investigated here in terms of equity) has a positive effect on all the aspects of engagement, including the emotional one. In line with this study, Molinari and Mameli (2018) have shown that teacher justice has a positive effect on emotional engagement. A number of studies have ascertained the importance of emotional engagement for adolescent health as well.…”
Section: Students' School-specific Well-being: Emotional Engagement Asupporting
confidence: 90%
“…In the 1960s Taylor (1962) claimed that, for students, justice is one of the most significant teacher qualities. More recently, some authors have put forward the idea that justice, in educational settings, should be conceived as a basic psychological need (Molinari & Mameli, 2018) which ought to be fulfilled to support students' intrinsic motivation, self-determination, and psychological growth.…”
Section: Teacher Justicementioning
confidence: 99%
“…We made use of the Italian translation (Molinari & Mameli, ) of the Activity Feeling State (AFS; Reeve & Sickenius, ; Reeve & Tseng, ), a 10‐item self‐report measure of perceived psychological need fulfilment. The instrument, starting with the stem ‘During class I feel…’, asks students to refer to their general perception of their own school experience.…”
Section: Methodsmentioning
confidence: 99%
“…There is no research, to our knowledge, that has explored the association between interpersonal justice and basic psychological needs. Only very recently, Molinari and Mameli () have advanced the argument that in school, as in other organizational contexts (Cropanzano, Byrne, Bobocel, & Rupp, ), justice should be considered as a condition sine qua non for the needs of autonomy, competence, and relatedness to be satisfied. From our point of view, the main question researchers should address in future investigations is a theoretical one: Can students perceive that their basic needs are fully recognized in teacher–student relationships that are not connoted by a fair interpersonal treatment?…”
Section: Introductionmentioning
confidence: 99%